The impact of digitalization on public administration, economic development, and well-being in the EU countries - Androniceanu, Armenia (Central European Public Administration Review, 2022)
Purpose : Digitalization has been the driving change in creating jobs and increasing economic growth in recent years. However, the digitalization of countries and sectors is uneven. The paper focuses on various factors that have an impact on the economic development and well-being in EU countries. Its purpose is to show the evolution of EU countries in terms of digital transformation and how other indicators, such as e-government, human development index, labour productivity, and economic growth influenced the well-being in EU countries in 2019–2021. Design/methodology/approach: The dataset consists of 15 numerical indicators extracted from Eurostat and World Bank databases. We apply principal component analysis and cluster analysis. Findings and Practical Implications: The main research results show that the first dimension – named the impact of innovation on well-being – is dominated by e-government, the percentage of ICT specialists in total, internet use by individuals, the Human Development Index, the Digitalization Index, the Happiness Indicator, human capital, and the integration of digital technology. The second dimension is characterized by government expenses and productivity. Finally, the third dimension is dominated by the GDP growth rate. 77.67% of the total variance is explained by the first three principal components. Originality: Four clusters have been identified by means of the K-Means clustering algorithm. All four clusters are well determined, with cluster 1 including the three Nordic countries ranking first, followed by cluster 3 of well-developed countries and cluster 4 containing mainly emerging economies.
Keywords: blaginja; digitalizacija; digitalization; economic growth; gospodarska rast; javna uprava; public administration; well-being